Action of the salivary microorganisms having sorbitol as substratum - Amaral, Fabricio Reskalla [UNESP]; Tonetto, Mateus Rodrigues; Pinzan-Vercelino, Celia Regina Maio; Silva, Monica Barros da; Assunção, Elida Lucia Ferreira [UNESP]; Bhandi, Shilpa H.; Andrade, Marcelo Ferrarezi de [UNESP]; Youssef, Michel Nicolau [UNESP]; Saad, José Roberto Cury [UNESP] (Jaypee Brothers Medical Publishing, 2014)
Microorganisms living in the saliva are able to ferment some sweetener types and to promote the fall of pH that has its critical point around 5.5; in this situation, they equal the input and the calcium output in the processes of remineralization and demineralization. For iteration of the three essential factors to the installation of the dental caries (microorganism, host and diet) suggested the accomplishment of a work that involved one of these factors. This work aims to study this issue, through the indication of substitute sweetener of the saccharose, whenever possible, it solved to evaluate pH of the saliva, exposed to sorbitol.
Keywords: Sorbitol; Sweetener and dental caries; Microorganism